Virologic and immunologic outcomes of the second-line regimens of antiretroviral therapy among HIV-infected patients in Thailand - May Myat Win (2018)
Goal of the second-line therapy among HIV-1-infected patients is to re-establish virological suppression, although treatment options in resource-limited settings are limited. An observational cohort of patients with first-line antiretroviral therapy (ART) failure was conducted in a university hospital in Thailand. Of 95 patients, mean age 39 years, 65% were male. Median CD4 and HIV-1 RNA at second-line ART initiation were 158 cells/mm 3 and 4.1 copies/mL, respectively. Boosted protease inhibitor plus 2 nucleoside reverse transcriptase inhibitors (NRTIs), indicated by genotype results, was commonly used as second-line regimen. At 6, 12, 24, and 36 months of second-line ART, 67%, 62%, 84%, and 90% of patients achieved HIV-1 RNA < 50 copies/mL; median CD4 were 258, 366, 444, and 522 cells/mm 3 , respectively. Good adherence, high baseline CD4, and early Centers for Centers for Disease Control and Prevention (CDC) staging were associated with virologic success (P < .05). Second-line ART based on the results of genotype testing yields the good virologic and immunologic outcomes in a resource-limited setting, and scaling-up of second-line ART is indicated. © The Author(s) 2011.